2015
DOI: 10.1038/ncomms7934
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specification of ovarian theca cells requires multicellular interactions via oocyte and granulosa cells

Abstract: Organogenesis of the ovary is a highly orchestrated process involving multiple lineage determinations of ovarian surface epithelium, granulosa cells, and theca cells. While the sources of ovarian surface epithelium and granulosa cells are known, the origin(s) of theca progenitor cells have not been definitively identified. Here we show that theca cells derive from two sources: Wt1+ cells indigenous to the ovary and Gli1+ mesenchymal cells migrated from the mesonephros. These progenitors acquire theca lineage m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 39 publications
6
172
0
3
Order By: Relevance
“…Other cells, such as the precursors of the steroidogenic cells, may also be an origin. Theca cells were recently reported to be derived from Wt1-positive cells indigenous to the ovary and Gli1-positive mesenchymal cells that have migrated from the mesonephros (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cells, such as the precursors of the steroidogenic cells, may also be an origin. Theca cells were recently reported to be derived from Wt1-positive cells indigenous to the ovary and Gli1-positive mesenchymal cells that have migrated from the mesonephros (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cells first appear in testes at E12.5, whereas theca-interstitial cells are observed postnatally in the ovaries along with the development of ovarian follicles. The origins of Leydig cells (Weaver et al, 2009;Barsoum and Yao, 2010;DeFalco et al, 2011) and theca cells (Liu et al, 2015) have been studied previously. However, the underlying mechanism that regulates the differentiation between supporting cells and steroidogenic cells during gonad development is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The dose (1 mg/mouse) and frequency (one injection) of the tamoxifen treatment induced recombination for ∼24 h, so that all tdTomato-positive cells are derived specifically from the WT1 + cell population between E10.5 and E11.5 (Liu et al, 2015). At E11.5, or 24 h after tamoxifen treatment, the lineagelabeled Wt1…”
Section: T2mentioning
confidence: 99%
“…The cDNA preparation was synthesized using random hexamers and the Superscript II cDNA synthesis system (Invitrogen) following manufacturer's instruction. Gene expression was analyzed by real-time PCR using the Bio-Rad CFX96 Real-Time PCR Detection system (Liu et al, 2015). Taqman probes (ThermoFisher Scientific), were used to examine the fold changes of the transcripts.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…The assembly of the follicles is completed by the recruitment of steroidogenic precursor cells to differentiate into theca cells [Hirshfield, 1991]. Recently, it has been shown that there are 2 sources of theca cell precursors: mesenchymal cells that reside within the ovary and a second population that migrates into the ovary from the mesonephros [Liu et al, 2015].…”
Section: Ovarian Developmentmentioning
confidence: 99%